DECOLONIZING CORDEL LITERATURE IN THE CLASSROOM: : ANALYSIS OF CURRENT SCIENTIFIC PRODUCTION (Interdisciplinary Studies Journal, 2026)
This study investigates the possibilities of incorporating Brazilian Cordel Literature (LCB) into a classroom context, adopting a decolonial approach to overcome the devaluation that often surrounds this genuinely Brazilian literary art, thus recognizing its authenticity, artistic, and historical value. The theoretical framework includes Marcia Abreu (1993), covering the singularity of Brazilian cordel, and Vera Maria Candau (2020), reflecting on the need for decolonial and intercultural education in order to deconstruct colonial patterns in teaching. The methodology employed was a systematic literature review, focused on the didactic-pedagogical potential of LCB from a decolonial perspective.
Keywords: Brazilian Cordel Literature; School; Decoloniality; Interculturality